Pengaruh Literasi Digital dan Media Pembelajaran Berbasis TIK Terhadap Kompetensi Pedagogik Guru PAI - Yadi, Supriyadi; Kusen; Anshori, Sakut (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2024)
PAI teachers' understanding of digital literacy and the use of learning tools is very important, which should be able to improve PAI teachers' pedagogical competence. This research aims to see the influence of digital literacy and TIK-based learning media on the pedagogic competence of Islamic Religious Education (PAI) teachers at MTs throughout Kepahiang Regency. This research uses quantitative research methodology. The sampling method used in this research was complete sampling, with a total of 33 PAI teachers from 99 MTs spread across Kepahiang Regency. Research found that PAI MTs teachers in Kepahiang Regency have a high level of digital literacy, with 86.5% of teachers aware of digital learning resources. They are able to use TIK-based learning materials, applications, social networks, and the internet to search for and provide learning media. The use of technology in the classroom is considered good, with an average score of 85.6%. PAI teachers demonstrate good educational skills, including assessing student skills, offering systematically structured learning, identifying learning problems, and evaluating learning effectively. Digital literacy has a significant impact on the pedagogical skills of PAI MTs teachers in Kepahiang Regency, increasing their pedagogical competence. TIK-based learning media improves learning design, communication, teamwork, and student knowledge development. However, teachers must continue to strengthen their technology skills to remain relevant in the digital era.